Connecting the complex dots: A review of urban change complexities in Ghana - Kwaku Owusu Twum; John Ayer (Cogent Social Sciences, 2019)
Contemporary urban literature addresses various dimensions of the urban space – from spatial reflective analysis of the urban landscape to its evolving human interactive changes. However, the spatio-temporal visibility of urban changes has been less attractive, perhaps due to the unnoticed connection of evolving patterns. Further, urban manifestation reviewed as a unitary system has poorly regarded the consideration for its growing complications. This makes it speciously difficult to significantly trace, track and transfer urban change information for policy guidance and effective decision-making. This paper attempts to address from a contextual study of urban Ghana, this disconnect by adopting a simulated systematic revision of literature. From a multi-diagnostic perspective, it assesses and reflects on the change indicator patterns over the country. Additionally, it reveals the spatial and social story behind the urban retrospect of Ghana and sets the pace of exploring the comprehensiveness of urban complexities using GIS. The paper underscores the significant challenges arising from the deficiency of data on empirical analysis of urban changes and the inefficient traditional monitoring methods affecting local decision-making. Conclusively, it supports the major contribution of advancing studies in the domain of geospatial technology as an organized strategy to make informed and effective urban multidimensional decisions.